Linking the patient experience of foot involvement related to psoriatic arthritis to the International Classification of Functioning, Disability and Health. Issue 2 (11th July 2020) - Carter, Kate; Tannous, Caterina; Walmsley, Steven; Rome, Keith; Turner, Deborah E
Abstract: Objective: The aim was to categorize the patient experience of PsA-related foot involvement by linking it to the International Classification of Functioning, Disability and Health (ICF) framework. Methods: Concepts, obtained from a previous qualitative investigation of people with PsA and health professionals into their perspective of PsA-related foot involvement, were linked to the full version of the ICF classification. Concepts were linked to the most appropriate ICF category using established linking rules, which enable a systematic and standardized linking process. All concepts were linked independently to the ICF by two investigators, followed by a third investigator for adjudication. The professional backgrounds of the investigators included occupational therapy and podiatry. Results: More than 100 distinct ICF categories were linked to the interview concepts. The most represented ICF category was body functions (35%), followed by environmental factors (31%), activities and participation (19%) and body structure (15%). Concepts that could not be linked to the ICF were related to coping, aspects of time and knowledge. Health professionals identified a greater proportion of body functions and fewer activity and participation categories compared with patients, indicating a possible mismatch of key concerns. Interdisciplinary group analysis demonstrated merit. Conclusion: A list of ICF categories was generated, defining aspects of functioning important and relevant to the impact of PsA-related foot involvement. Despite the localized anatomical focus of this study, the effect of foot problems in PsA was linked to all components of the ICF, confirming the profound impact on functioning and daily life.